Cavitary pulmonary lesions in systemic lupus erythematosus: an unusual manifestation - Amir Reza Dalili; Reza Lotfi; Seyedeh Maryam Mousavi (Electronic Physician, 2014)
Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown pathogenesis. The frequency of SLE with cavitary lesion manifestation is very rare and is thought to be due to infection or pulmonary embolism. A 19- year-old female diagnosed with SLE complicated by lupus nephritis and cavitary pulmonary lesion is presented in this case report. Other diseases that can lead to such lesions were ruled out in the patient. The patient improved briefly after the initiation of immunosuppressive therapy, but was unresponsive to supportive treatment due to pneumothorax. Pneumothorax is caused by cavitary lesions and possibly bronchopleural fistulas – these later caused respiratory distress and death. The patient did not show any improvement in the lesions after the initiation of immunosuppressive therapy. This case report suggests that the differential diagnosis of cavitary lung lesions should include SLE